Optimizing Cotton Row Configuration in Jujube–Cotton Intercropping Systems Improves Their Productivity, Net Effects, and Sustainability - Jinbin Wang; Guodong Chen; Peijuan Wang; Zhengjun Cui; Sumei Wan; Yunlong Zhai; Tiantian Li; Yaru Zhao (Agronomy, 2024)
The bare row spacing between young jujube trees reduces resource use efficiency. Planting cotton between rows of jujubes can improve the efficiency of light, heat, water, and temperature resources. However, it is not clear how many rows of cotton between the jujube rows would be the most suitable pattern. A field study with different cropping systems was performed to investigate the land equivalent ratio (LER), the competition of cotton to jujube, and the sustainability index. The treatments included (1) monoculture jujube, (2) monoculture cotton, (3) jujube intercropped with two rows of cotton (J/C2), (4) jujube intercropped with four rows of cotton (J/C4), and (5) jujube intercropped with six rows of cotton (J/C6). The results showed that the LER under the J/C2, J/C4, and J/C6 systems were 1.17, 1.30, and 1.28, respectively. The LER and total yield were higher under J/C2 than under the J/C4 and J/C6 treatments. The overyielding rate of cotton was increased, while those of jujube were decreased with increasing rows of cotton. The competition between cotton to jujube was less than 0. The net, complementarity, selection effect, and sustainability index were significantly higher under J/C4 and J/C6 than under J/C2, with J/C4, showing stronger net effects. Both complementarity and selection effects contributed to the intercropping yield advantages. Comprehensively considering yield, economic efficiency, sustainability index, land use efficiency, and net effect, J/C4 is one of the most productive and sustainable planting patterns of jujube–cotton intercropping system in southern Xinjiang, which is the more ideal pattern in arid and semi-arid regions.